2019
DOI: 10.1002/jcp.29045
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0000745 promotes cervical cancer by increasing cell proliferation, migration, and invasion

Abstract: Circular RNAs (circRNAs) participate in gene regulation and malignant tumor progression, including uterine cervical cancer (CC). In this study, the expression profile of circRNAs in CC was detected using circRNA microarrays. Then, we selected hsa_circ_0000745 for further examination from the significantly dysregulated circRNAs.Proliferation assays, Transwell assays, quantitative reverse transcription polymerase chain reaction, western blot analysis and tumorigenesis tests in vivo were used to validate the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 29 publications
(34 reference statements)
0
70
0
Order By: Relevance
“…Of them, Liu Y et al reported that circular RNA hsa_circ_0008039 promotes breast cancer cell proliferation and migration by modulating miR‐432‐5p/E2F3 axis and hence may be a potential therapeutic target 42 . Huang et al argued that hsa_circ_000074, as a tumor promoter in CC, enhances the cellʹs ability to proliferate, migrate, and invade by reducing the expression of E‐cad and is a candidate target for the therapy of CC in the clinic 43 . It has been confirmed that hsa_circ_0001946 has been also reported to be extremely downregulated in ESCC tissues by Fanʹs teams 44 and in NSCLC samples by Huangʹs group 45 using another microarray platform and RNA sequencing technology, which confirms the accuracy of our microarray result and potentially implies the crucial role of circ_0001946 in the development of BC as well.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, Liu Y et al reported that circular RNA hsa_circ_0008039 promotes breast cancer cell proliferation and migration by modulating miR‐432‐5p/E2F3 axis and hence may be a potential therapeutic target 42 . Huang et al argued that hsa_circ_000074, as a tumor promoter in CC, enhances the cellʹs ability to proliferate, migrate, and invade by reducing the expression of E‐cad and is a candidate target for the therapy of CC in the clinic 43 . It has been confirmed that hsa_circ_0001946 has been also reported to be extremely downregulated in ESCC tissues by Fanʹs teams 44 and in NSCLC samples by Huangʹs group 45 using another microarray platform and RNA sequencing technology, which confirms the accuracy of our microarray result and potentially implies the crucial role of circ_0001946 in the development of BC as well.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating experiments indicate that circRNAs can function as biomarkers for cancer diagnosis and potential therapeutic targets [5]. For instance, circ_0000745 enhances cervical cancer (CC) cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) [6]; circ_0058124 facilitates the progression of papillary thyroid carcinoma by modulating the NOTCH3/GATAD2A axis [7]; circ-SERPINE2 up-regulates the expression of YWHAZ and promotes the progression of gastric cancer [8]. However, the researches on expression function and mechanism of circRNA in RB are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al (49) demonstrated that circ-ATP8A2 was upregulated in cervical cancer tissues and cell lines, and further confirmed that high levels of circ-ATP8A2 were associated with a higher FIGO stage, positive lymph node invasion and myometrial invasion. In addition, has-circ-u0000745 was upregulated in cervical cancer tissues and cell lines, which was found to be correlated with various clinicopathological features, such as poorly differentiated tumors and positive vascular/lymphatic invasion (45). Another circRNA, circ_0005576, has been associated with a higher pathological stage and lymph node metastasis (50).…”
Section: Iii) Circrnas As Biomarkers Of Cervical Cancer Metastasismentioning
confidence: 99%
“…Gao et al (44) conducted a high-throughput microarray study using four pairs of cervical cancer and adjacent noncancerous tissues, revealing 19 downregulated and 26 upregulated circRNAs in cervical cancer. Jiao et al (45) studied circRNA expression profiles using microarray analysis, and found that 178 circRNAs were differentially expressed between cervical cancer and matched normal cervical tissues, of which 101 were downregulated and 77 were upregulated. By classifying the 77 upregulated circRNAs, they also identified 68 exonic, 3 intronic, 1 antisense and 5 intragenic circRNAs in cervical cancer tissues, as well as 101 downregulated circRNAs (including 81 exonic, 13 intronic, 3 antisense and 4 intragenic variants).…”
Section: Expression Of Circrnas In Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation